Flow visualization of downhill ski racers using computational fluid dynamics - Asai, T.; Hong, S.; Ijuin, K. (Procedia Engineering, 2016)
In downhill alpine skiing, racers often exceed speeds of 120 km/h, with air resistance substantially affecting the overall race times. To date, studies on air resistance in alpine skiing have used wind tunnels and actual skiers to examine the relationship between the gliding posture and magnitude of drag, as well as for the design of skiing equipment. However, these studies have not revealed the flow velocity distribution and vortex structure around the skier. In the present study, we used computational fluid dynamics with the lattice Boltzmann method to derive the relationship between flow velocity in the full tuck position (the downhill racer's speed) and total drag. Furthermore, we visualized the flow around the downhill racer and examined its vortex structure. The results show that the total drag force in the downhill racer model is 27.0 N at a flow velocity of 15 m/s, increasing to 185.8 N at 40 m/s. Moreover, the visualization of the flow field indicates that the primary drag locations at a flow velocity of 40 m/s are the head, upper arms, lower legs, and thighs (including the buttocks).